Social Capital Dynamics in Seaweed Cultivation in Bonto Jai Village, Bissappu District, Bantaeng Regency - Asrina Asrina; Andi Amri; Abdul Wahid; Arie Syahruni Cangara; Muhammad Dalvi Mustafa; Firman Firman (PONGGAWA : Journal of Fisheries Socio-Economic, 2025)
Social capital is a resource formed from interactions within a community, creating emotional bonds and cooperation that support the success of seaweed cultivation. This study aims to analyze the dynamics of social capital and its impact on the socio-economic aspects of coastal communities. This study was conducted in September 2024-October 2024. This study uses a qualitative descriptive method, with data collection through in-depth interviews, observation, and documentation. Key informants consisted of the head of the Abbulo Sibatang cultivation group, village heads, collectors, and ordinary informants consisting of seaweed farmers. Informants directly involved in seaweed cultivation activities. In this study, 17 seaweed cultivators in Bonto Jai Village were used as regular informants. The results of the study show that social capital plays an important role in business sustainability. Trust strengthens cooperation and resource sharing, social norms such as mutual cooperation increase solidarity, while social networks facilitate market access and external support. The impact is seen in increased income, business stability, and closer social relationships in coastal communities. Conclusion The dynamics of social capital of seaweed farmers in Bonto Jai Village are influenced by strong trust, norms, and social networks. Social bonding, social bridging, and social linking strengthen cooperation, information exchange, and community economic stability. Seaweed cultivation has a positive impact on the community economy, increasing income, welfare, and access to education. However, land conflicts and profit distribution remain challenges. Strengthening social capital through training and community empowerment is needed to maintain socio-economic balance and business sustainability.